2021
DOI: 10.1002/cam4.4419
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation test on fine‐needle aspiration specimens of thyroid nodules: Clinical correlations for 4600 patients

Abstract: Background:The BRAF V600E mutation is valuable for the diagnosis, prognosis, and therapy of papillary thyroid cancer (PTC). However, studies related to this mutation have involved only a small number of patients. Therefore, we performed a large-scale analysis from a single institute to evaluate the accuracy of combined fine-needle aspiration (FNA) and BRAF V600E mutation tests for PTC diagnosis.Methods: A total of 4600 patients with thyroid nodules who underwent both FNA cytology and BRAF V600E mutation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
2
9
1
Order By: Relevance
“…The accuracy of cytological diagnosis remarkably depends on the experience of the pathologists and the sample quality, while BRAF V600E analysis only needs an appropriate sample and standardized test method. It is reported that the sensitivity of FNA-BRAF V600E mutation test varies from 32% to 82%, 26 which is less than that in our study. The reasons for this may be ethnic differences mentioned above and other non-classical PTC subtypes which seldom carry BRAF mutation.…”
Section: Discussioncontrasting
confidence: 86%
“…The accuracy of cytological diagnosis remarkably depends on the experience of the pathologists and the sample quality, while BRAF V600E analysis only needs an appropriate sample and standardized test method. It is reported that the sensitivity of FNA-BRAF V600E mutation test varies from 32% to 82%, 26 which is less than that in our study. The reasons for this may be ethnic differences mentioned above and other non-classical PTC subtypes which seldom carry BRAF mutation.…”
Section: Discussioncontrasting
confidence: 86%
“…BRAF genetic test was valuable for the diagnosis, prognosis, and therapy of PTC ( 19 ). In addition, some scholars revealed that BRAF mutations were associated with markers of clinical aggressiveness such as larger tumors, lymph node metastases, and poor clinical outcomes ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we advocate that LBP slides and conventional smears should be applied together, combined and complementary to each other. In addition, we evaluated the gene detection of the same group of cases and found that the sensitivity was 78.34%, which was slightly higher than that reported (76.71%) in the literature [ 19 ]. At the same time, it also suggests that gene detection cannot solve all PTC cases.…”
Section: Discussionmentioning
confidence: 98%